KOMITMEN, IKLIM ORGANISASI, KOMUNIKASI, INOVASI DAN EFEKTIVITAS ORGANISASI - Ni Made Suntriani (Universitas Pendidikan Nasional, 2013)
The research was based on the fact that human resources have differences in attitudeand experiences as an actor of organization. The differences caused every person whoperformed activities in organization have different ability and performances as well onvacation. The research was done at Ministry of Religion office Education and TrainingCentre Denpasar, the research were to find out the effectiveness of commitment, organizationclimate, communication, innovation and organization effectiveness. Respondents of thisresearch were the Employees of Ministry of Religion office Education and Training CentreDenpasar, consist of 137 people. The data were collected by distributed the questionnairewhich consist of 27 questions, each of it used 10 alternative answer questions. The Analysisof the data were used to answer the research question and hypothesis testing of effectivenesscommitment, organization climate, communication, innovation and effectivenessorganization, the researcher used statistical methods and structural equation modeling(SEM) with AMOS Software version 16.0Keywords: commitment, organization climate, communication, innovation andorganization effectiveness